OC-022 Multicentre comparison of the Glasgow Blatchford and Rockall scores in the prediction of clinical endpoints in upper gastrointestinal haemorrhage. (23rd September 2015) - Stanley, A J; Dalton, H; Blatchford, O; Ashley, D; Mowat, C; Cahill, A; Gaya, D R; Warshow, U; Thompson, E; Groome, M; Benson, G; Murray, W
Abstract : Introduction: The pre-endoscopic Glasgow Blatchford Score (GBS) can identify low-risk patients with upper gastrointestinal haemorrhage (UGIH) who may be suitable for out-patient management. Although it does not include the patient's age, the GBS appears to have high accuracy in predicting clinically relevant endpoints. Our aim was to compare the GBS with both the pre-endoscopy (admission) and post-endoscopy (full) Rockall scores in predicting need for clinical intervention and mortality. Methods: Data on consecutive patients presenting to four UK hospitals (Glasgow Royal Infirmary, Royal Cornwall Hospital Truro, University Hospital of North Tees and Ninewells Hospital Dundee) were collected. Admission history, clinical and laboratory data, endoscopic findings and treatment, and clinical follow-up were recorded. We used ROC curves to compare the three scores in the separate prediction of death, endoscopic or surgical intervention and transfusion. Results: 1556 patients (mean age 56.7 years; 62% male) presented with UGIH to the four hospitals during the study period. 74 (4.8%) died, 223 (14.3%) had endoscopic or surgical intervention and 363 (23.3%) required transfusion. The GBS was equally effective at predicting death compared with both the admission Rockall score (area under ROC curve 0.804 vs 0.801) and the full Rockall score (AUROC 0.741 vs 0.790). In predicting endo/surgical intervention, the GBS was superior to the admission Rockall score (AUROC 0.858 vs 0.705, p<0.00005) but similar to the full Rockall score (AUROC 0.822 vs 0.797). The GBS was superior to both the admission Rockall (AUROC 0.944 vs 0.756, p<0.00005) and the full Rockall score (AUROC 0.935 vs 0.792, p<0.00005) in predicting need for transfusion. Conclusion: Despite not incorporating age, the GBS is as effective as the admission and full Rockall scores in predicting death after UGIH. It is superior to both the admission and full Rockall scores in predicting need for transfusion and superior to the admission Rockall score in predicting endoscopic or surgical intervention.